ADHD and autism in Neurocognitive Mismatch Theory: distinct neurodevelopmental incompatibilities with the market-based system - Joseph Lewis Kidwell (Frontiers in Psychology)
ADHD and Autism Spectrum Disorder (ASD) represent distinct neurodevelopmental conditions with unique profiles, yet they share susceptibility to environmental pressures that may exacerbate cognitive mismatches. This paper argues that Attention-Deficit/Hyperactivity Disorder and Autism Spectrum traits are not fixed neurological disorders but neurodevelopmental variants destabilized by the sociobiological mismatch between evolved human cognition and the pressures of modern market-based civilization. Drawing on evolutionary biology, developmental neuroscience, social epidemiology, and political economy, the paper reframes these conditions as context-contingent outcomes: traits that are biologically conserved due to their adaptive value in ancestral environments but rendered dysfunctional under chronic stress, inequality, overstimulation, environmental toxicity, and cognitive suppression endemic to industrial societies. It synthesizes evidence across prenatal programming, intergenerational stress transmission, pharmaceutical ethics, and neuroplastic adaptation to propose an ecological model in which the environment, not the brain, is the primary source of pathology. This reframing calls for systemic transformation, not individual correction, and provides a foundation for more inclusive, developmentally respectful, and ecologically coherent mental health paradigms.